(untitled) (Itinera, 2024)
Delbono’s production lends itself effectively and almost emblematically to a reflection on the active character of mimesis because it is characterized by a sort of duplicity: both his cinema and his theatre are marked by an apparently documentary or performative manner, a flagrantness and immediacy that allude to the presence, to the being of the actor “here and now” – a here and now expressed differently in cinema and theatre – without however being reduced to a purely testimonial attitude. Pippo Delbono’s entire life and performing arts journey can be read in the light of an incessant montage practice. In this sense, montage is the most vital manifestation of active mimesis as a conditio humana.